Design used in complex sentences of chinese language - shermentaeva, Sh. D.; Abdraimova, N. B. (Journal of Oriental Studies, 2016)
this article discusses the framework used in the design of complex offers Chinese language. the focus is on the comparative analysis of frame structures in slozhnosochinennyh and compound sentences of Chinese and russian language, highlighting the ones most commonly used design.